Strength and endurance training reduces the loss of eccentric hamstring torque observed after soccer specific fatigue - Matthews, M. J.; Heron, K.; Todd, S.; Tomlinson, A.; Jones, P.; Delextrat, A.; Cohen, D. D. (Physical Therapy in Sport, 2017)
Objectives: To investigate the effect of two hamstring training protocols on eccentric peak torque before and after soccer specific fatigue. Participants: Twenty-two university male soccer players. Design: Isokinetic strength tests were performed at 60 /s pre and post fatigue, before and after 2 different training interventions. A 45-min soccer specific fatigue modified BEAST protocol (M-BEAST) was used to induce fatigue. Players were randomly assigned to a 4 week hamstrings conditioning intervention with either a maximum strength (STR) or a muscle endurance (END) emphasis. Main outcome measures: The following parameters were evaluated: Eccentric peak torque (EccPT), angle of peak torque (APT), and angle specific torques at knee joint angles of 10, 20, 30, 40, 50, 60, 70, 80 and 90. Results: There was a significant effect of the M-BEAST on the Eccentric torque angle profile before training as well as significant improvements in post-fatigue torque angle profile following the effects of both strength and muscle endurance interventions. Conclusions: Forty-five minutes of simulated soccer activity leads to reduced eccentric hamstring torque at longer muscle lengths. Short-term conditioning programs (4-weeks) with either a maximum strength or a muscular endurance emphasis can equally reduce fatigue induced loss of strength over this time period.